Bioherbicidal activity of Streptomyces spp isolated from tobacco rhizosphere against certain dicot and monocot weeds - SUBHASHINI, D V (The Indian Journal of Agricultural Sciences, 2013)
A bioherbicide is a biologically based control agent for weeds that utilize such naturally occurring enemies, rather than depending on man-made chemicals. Out of 12 isolates of Streptomyces spp. obtained from tobacco rhizosphere two isolates (SI and SII) were found to be efficient in suppressing the weeds. Growth pattern of the isolates was studied. Isolate SII was found to be more effective against weeds. Weedicidal activity of Streptomyces was tested against two dicot and two monocot weeds of tobacco fields, viz. Solanum nigrum, Sorghum halepense, Eleusine indica and Euphorbia hirta. Streptomyces Isolate SII showed faster growth and effective bioherbicidal activity. There was a significant and progressive reduction in dry weight of all the weed species treated with the extracts of 3 to 9 day old cultures of Streptomyces isolate SI and SII. The reduction in dry weight was better in case of isolate SII than isolate SI and the dry weight reduction was comparable with 2,4-D.